The Impact of Artificial Intelligence Adoption on Employee Performance, Reskilling, and Well-Being at XYZ Company - Umar Umar; Ibrahim Ibrahim; Mansur Mansur (GENTARA: management and accounting research, 2026)
This study examines the impact of artificial intelligence (AI) adoption on employee performance, reskilling, and well-being at XYZ Company. Grounded in a human-centered human resource management perspective, the study addresses the growing need to understand how AI influences not only organizational efficiency but also employees’ development and work experience. A quantitative approach was employed using survey data collected from employees who were directly exposed to AI-enabled work processes. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the proposed relationships among variables. The findings indicate that AI adoption has a positive and significant effect on employee performance, reskilling, and well-being, with the strongest effect observed on reskilling. These results suggest that AI adoption functions not merely as a technological tool, but as a broader organizational transformation that shapes productivity, learning readiness, and employee sustainability. This study contributes to the human resource management literature by offering an integrated framework that connects technological adoption with performance, capability development, and well-being. Practically, the findings highlight the importance of combining AI implementation with supportive learning systems and employee-centered management practices